Pemanfatan Limbah Tongkol Jagung Sebagai Bahan Pembuatan Bangke, Kudapan Kaya Serat dan Protein - Widiati, Bibiana Rini; Haerul, Haerul; Sadat, Moh. Anwar (Abdimas Universal, 2025)
The potential of corn cob waste, which has low-calorie characteristics and is rich in fiber, can be processed into an alternative fiber- and protein-rich snack. The purpose of this community service activity is to utilize corn cob waste as an effort to diversify food and improve the skills of partners in processing corn cob waste into "bangke" snacks for the Anggrek Women's Farmer Group (WFG) in Rompegading Village, Cenrana District, Maros Regency. The method used to collect data is the survey method, while the data analysis applied includes both qualitative and quantitative approaches. Quantitative analysis is conducted to determine the extent of skill improvement among partners regarding the implementation of the program by distributing questionnaires, then quantifying the results into percentages and describing them. The results of the community service indicate that corn cobs can be processed into fiber- and protein-rich bangke snacks. The proximate analysis results show that bangke made from corn cobs contains 7.96% crude protein, 9.96% crude fat, and 1.77% fiber. Organoleptic testing of bangke from corn cobs shows that over 86% of the community prefers it in terms of color, texture, taste, and aroma. This activity has also enhanced the skills of the community, especially the Anggrek Women's Farmer Group (KWT), in making bangke from corn cobs. The pre-test score of 62% and post-test score of 86% indicate that participants have generally become proficient in making bangke snacks.